A comparison of four different approaches to measuring health utility in depressed patients - Turner, Nicholas (BioMed Central, 2013)
BACKGROUND: A variety of instruments are used to measure health related quality of life. Few data exist on the performance and agreement of different instruments in a depressed population. The aim of this study was to investigate agreement between, and suitability of, the EQ-5D-3L, EQ-5D Visual Analogue Scale (EQ-5D VAS), SF-6D and SF-12 new algorithm for measuring health utility in depressed patients. METHODS: The intraclass correlation coefficient (ICC) and Bland and Altman approaches were used to assess agreement. Instrument sensitivity was analysed by: (1) plotting utility scores for the instruments against one another; (2) correlating utility scores and depressive symptoms (Beck Depression Inventory (BDI)); and (3) using Tukey’s procedure. Receiver Operating Characteristic (ROC) analysis assessed instrument responsiveness to change. Acceptability was assessed by comparing instrument completion rates. RESULTS: The overall ICC was 0.57. Bland and Altman plots showed wide limits of agreement for each pair wise comparison, except between the SF-6D and SF-12 new algorithm. Plots of utility scores displayed ’ceiling effects’ in the EQ-5D-3L index and ’floor effects’ in the SF-6D and SF-12 new algorithm. All instruments showed a negative monotonic relationship with BDI, but the EQ-5D-3L index and EQ-5D VAS could not differentiate between depression severity sub-groups. The SF-based instruments were better able to detect changes in health state over time. There was no difference in completion rates of the four instruments. CONCLUSIONS: There was a lack of agreement between utility scores generated by the different instruments. According to the criteria of sensitivity, responsiveness and acceptability that we applied, the SF-6D and SF-12 may be more suitable for the measurement of health related utility in a depressed population than the EQ-5D-3L, which is the instrument currently recommended by NICE.